Batalnya Perkawinan Karena Tidak Adanya Izin Poligami (Analisis Putusan Pengadilan Agama Nomor 1859/PDT.G/2021/PA.STB.) - Muhammad Rizqi Iqbal; Sudianto; Muhammad Habib (Peduli Riset dan Pengabdian Masyarakat, 2024)
Marriage has no time limit, marriage must be eternal, unless due to something outside the wishes of the parties. The causes of dissolution of marriage ties are: Life Divorce, Death Divorce, Marriage Cancellation. The research approach used by researchers in this research is normative theological and normative juridical. The method used in this research is a qualitative method. Research using qualitative methods is research that tries to understand phenomena in their natural settings and contexts (not in the laboratory) where the researcher does not attempt to manipulate the observed phenomena. This research was carried out by reading and analyzing various existing literature, in the form of the Al-Qur'an, hadith, statutory regulations and laws contained in the compilation of Islamic Law, as well as the results of previous research. This research concludes that a marriage is invalid and can be annulled if it does not meet the requirements of a marriage, in this case an annulment of the marriage can only be carried out. Cancellation of a marriage in Islamic law is called fasakh which means to destroy or annul. Fasakh according to the language means damaged, void. Void is the destruction of the law that has been established for a person's practice, because it does not meet the requirements and harmony. In the marriage annulment law, it is regulated in Law number 1 of 1974 concerning marriage, contained in articles 22 to 28. In decision number 1859/Pdt.G/2021/Pa.Stb. It was found that a second marriage where the husband did not have permission from the first wife obtained through a religious court was in accordance with statutory regulations that could apply for an annulment of the marriage if the marriage requirements were not met.